The geopolitics of hydrogen : technologies, actors and scenarios until 2040 - Pepe, Jacopo Maria; Ansari, Dawud; Gehrung, Rosa Melissa (2023)
Zusammenfassung: The transition to a hydrogen-based economy is gaining momentum in both Germany and the European Union (EU). Used as an energy carrier, hydrogen holds the promise of freeing hard-to-decarbonise sectors like heavy industry, aviation, and maritime trade from their emissions. At the same time, policymakers hope that hydrogen will promote Europe’s energy independence, push sustainable development, and strengthen value-based trade. This study presents three plausible yet disruptive scenarios for the geopolitics of hydrogen up to the year 2040 (developed with a team of experts in a multi-stage foresight process). "Hydrogen Realignment" considers the possibility of an eastward shift of industry, power, and technological leadership; "Hydrogen (In)Dependence" depicts a future, in which Europe pursues hydrogen self-sufficiency but becomes dependent on raw material supply; and "Hydrogen Imperialism" delves into the dystopian scenario of a hydrogen transition dominated by hegemons and despots. The transition to hydrogen is likely to shift and complicate Europe’s external dependence rather than eliminate it; the role of supply chains will become more important. Moreover, the potential of hydrogen trade for global sustainable development is limited and requires targeted efforts. Resource distribution, production potential, current geopolitical power dynamics, and their interplay will influence hydrogen policy and decision-making along the entire value chain, with actors often giving priority to socioeconomic, geopolitical, and technopolitical considerations. Germany and the EU must pursue a proactive hydrogen strategy, acknowledge the preferences of external actors, and form pragmatic partnerships to keep sight of climate goals, retain industry, and avoid losing global influence. In addition to promoting targeted technologies, decision-makers must manage dependencies across sectors and do so in an anticipatory way. Pursuing diversification is indispensable, and instituting targeted diplomacy and development assistance would be helpful. The new hydrogen sector also needs governing institutions - for example a "Hydrogen Alliance" - to mitigate geopolitical risks and allocate investments correctly